2022
DOI: 10.3389/fpsyg.2021.771095
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Psychometric Properties of the Minnesota Living With Heart Failure Questionnaire in Individuals With Coronary Artery Disease in Lithuania

Abstract: BackgroundHealth-related quality of life (HRQoL) is known to be impaired in individuals with coronary artery disease (CAD), especially in those after a recent acute coronary syndrome (ACS). Heart failure (HF) is a common burden in this population that significantly contributes to worsening HRQoL. To accurately measure the level of HRQoL in individuals with CAD after ACS, disease-specific scales, such as the Minnesota living with heart failure questionnaire (MLHFQ), are recommended. Nevertheless, to date, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Quality of life assessment encompasses the use of generic and specific questionnaires. Notably, within the realm of specific assessments, the MLHFQ, pioneered by Rector, is the preeminent choice (14). Our results revealed that patients with an unchanged or increased MLHFQ score of less than 10 points at the fourth visit exhibited a statistically significant history of previous myocardial infarction (MI) and significant coronary artery disease (CAD).…”
Section: Discussionmentioning
confidence: 95%
“…Quality of life assessment encompasses the use of generic and specific questionnaires. Notably, within the realm of specific assessments, the MLHFQ, pioneered by Rector, is the preeminent choice (14). Our results revealed that patients with an unchanged or increased MLHFQ score of less than 10 points at the fourth visit exhibited a statistically significant history of previous myocardial infarction (MI) and significant coronary artery disease (CAD).…”
Section: Discussionmentioning
confidence: 95%
“…However, these studies did not evaluate the validity and reliability of the SF-36 scale in these patients. While previous research has demonstrated good validity and reliability of the SF-36 in assessing the quality of life in patients with coronary heart disease, [ 6 ] there is a lack of such evaluation in patients with sick sinus syndrome. Given the importance of understanding outcomes across age groups and disease stages from HRQoL in clinical decision-making, further investigation into HRQoL in sick sinus syndrome (SSS) patients is warranted.…”
Section: Introductionmentioning
confidence: 99%